Transfusion-transmitted hepatitis E - LI Baixun; LIU Tianxu; HUANG Liqin; DANG Yingnan; WANG Lin (Zhongguo shuxue zazhi, 2025)
Hepatitis E is an acute and self-limiting viral hepatitis caused by the hepatitis E virus (HEV). It has a higher mortality rate among immunosuppressed patients and pregnant women infected with HEV. Although HEV infections in humans are mostly caused by contaminated water or food worldwide, the incidence of transfusion-transmitted hepatitis E is continuously rising. Additionally, the prevalence of serum anti-HEV IgG in the blood donors in China is at a relatively high level, making it worth considering screening blood donors for HEV. This article briefly reviews the globally reported cases of transfusion-transmitted hepatitis E and the HEV screening strategies for blood donations.